INOVASI DALAM PEMASARAN : MENGUKUR KINERJA DAN MENINGKATKAN EFISIENSI SERTA PRODUKTIVITAS BISNIS DENGAN MENGGUNAKAN SISTEM MPA - Putri Zega, Wendy Teguh; Napitupulu, Viony Natasya; Saribu, Ardin Dolok; D. Siahaan, Ruth Dwi; Manullang, Tassya Teresa; Marpaung, Irma; R. Rajagukguk, Alda; Simorangkir, Patar (Jurnal Daya Saing, 2025)
Innovation in marketing is a critical element in maintaining business competitiveness in the digital era. This study aims to analyze the role of the Marketing Performance Assessment (MPA) system in measuring marketing performance and enhancing business efficiency and productivity. The study employs a literature review method with a descriptive qualitative approach to examine relevant theories and previous research findings. The results indicate that the MPA system provides a comprehensive overview of marketing performance through financial and non-financial indicators, such as customer satisfaction, loyalty, and organizational adaptability. This system functions not only as a measurement tool but also as an organizational learning mechanism that supports data-driven decision-making. However, the implementation of the MPA system still faces several challenges, including the lack of applicable quantitative indicators and limited focus on the long-term impact of marketing strategies. Therefore, developing a more contextual and operational MPA system is essential to support effective and sustainable marketing management across various industry sectors.